Quantifying regional, seasonal and interannual contributions of environmental factors on isoprene and monoterpene emissions estimates over eastern Texas. (April 2015) - Huang, Ling; McGaughey, Gary; McDonald-Buller, Elena; Kimura, Yosuke; Allen, David T.
Abstract: Recent years have brought renewed attention to the effects of drought on emissions of biogenic volatile organic compounds. Variability in environmental inputs that influence isoprene and monoterpene emissions within eastern Texas was quantified by examining seasonal and interannual changes in activity factors intrinsic to the Model of Emissions of Gases and Aerosols from Nature (MEGAN) during years that included average-to-wet conditions (2007) and extreme drought and heat (2006 and 2011). Activity factors are used in MEGAN to multiplicatively adjust emissions rates from an assumed set of standard conditions for temperature, light, leaf area index (LAI), and soil moisture. Temperature was found to be the primary driver of seasonal and interannual variations of isoprene and monoterpene emissions; during drought years, reductions in LAI were dominated by predicted emissions increases caused by much warmer temperatures. The response of biogenic emissions to soil water stress is a major source of uncertainty. Dependent on the specific soil moisture database employed, predicted reductions in isoprene emissions ranged from minimal to −70% during the summer of 2011, a period characterized by all-time record drought in the South Central U.S. Highlights: Eastern Texas has diverse land cover and climatology with recent severe drought. Temperature was a primary driver of variations in predicted biogenic emissions. The response of biogenic emissions to soil water stress is a source of uncertainty.